Efficient biosynthesis of levan from sucrose by a novel levansucrase from Brenneria goodwinii. (10th February 2017) - Liu, Qian; Yu, Shuhuai; Zhang, Tao; Jiang, Bo; Mu, Wanmeng
Highlights: A novel levansucrase was characterized from B. goodwinii. The polysaccharide biosynthesized from sucrose was determined to be levan. The enzyme displayed maximal transfructosylation activity at pH 6.0 and 35 °C. The enzyme produced 185 g/L levan from 50% (w/v) sucrose. The molecular weight of the produced levan reached 1.3 × 10 8 Da. Abstract: Levan, a unique homopolysaccharide consisting of fructose residues linked by β-(2, 6) bonds, possess promising physiochemical and physiological properties with numerous potential applications. In this study, a novel levan-producing levansucrase was characterized from Brenneria goodwinii . The polysaccharide produced by the recombinant enzyme from sucrose was structurally determined to be levan-type fructan connected by β-(2, 6) linkages. The optimum pH was measured to be pH 6.0 for both sucrose hydrolysis and transfructosylation. The optimum temperature was 35, 45, and 40 °C for transfructosylation, sucrose hydrolysis, and total activity, respectively. Higher sucrose concentration greatly favored to levan biosynthesis. The purified recombinant enzyme produced 185 g/L levan from 50% (w/v) sucrose at pH 6.0 and 35 °C for 12 h. The molecular weight of the produced levan polysaccharide reached 1.3 × 10 8 Da, which was much higher than the ones produced by many reported levansucrases.